Liberalizing world trade Development policy issues series - Bela Blassa; Michalopoulos, Constantine (U.S. : World bank, 1985)
This paper demonstrates that multilateral trade liberalization is in the mutual interests of the developed and the developing countries.
includes references
gau 01/03/17
loans
Keywords: Discussion paper; America